2005
DOI: 10.1128/mcb.25.23.10665-10673.2005
|View full text |Cite
|
Sign up to set email alerts
|

Autorepression of Rfx1 Gene Expression: Functional Conservation from Yeast to Humans in Response to DNA Replication Arrest

Abstract: The yeast Saccharomyces cerevisiae Crt1 transcription repressor is an effector of the DNA damage and replication checkpoint pathway. Crt1 binds and represses genes encoding ribonucleotide reductase (RNR) and its own promoter, establishing a negative-feedback pathway. The role of Rfx1, the mammalian Crt1 homologue, remained uncertain. In this study we investigated the possibility that Rfx1 plays a similar function in animal cells. We show here that, like Crt1, Rfx1 binds and represses its own promoter. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 50 publications
3
62
2
Order By: Relevance
“…The R2 gene is under repression by the Rfx1 transcription factor. 11 This mechanism of R2 repression was first identified in yeast where the Rfx1 ortholog, Crt1, represses the R2 gene. 29 Consistent with this repression role of Rfx1, chromatin immunoprecipitation (ChIP) analysis revealed that Rfx1 was bound to the R2 promoter more effectively in the quiescent cells than in the proliferative cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The R2 gene is under repression by the Rfx1 transcription factor. 11 This mechanism of R2 repression was first identified in yeast where the Rfx1 ortholog, Crt1, represses the R2 gene. 29 Consistent with this repression role of Rfx1, chromatin immunoprecipitation (ChIP) analysis revealed that Rfx1 was bound to the R2 promoter more effectively in the quiescent cells than in the proliferative cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) was performed as described. 11 Western Blotting. Western blotting (protein immunoblotting) was performed as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Rfx1 has been implicated in DNA damage recognition, and it is also a downstream target of the DNA damage sensor ATR kinase. 20 Rfx1 upregulation might be as follows: ATR is induced by DNA damage caused by IR, then ATR acts on its downstream targets including Rfx1. Upregulation of Rfx1 consequentially upregulates miR-709, which then inhibits the translation of BORIS and affects DNA methylation process in the germline (Fig.…”
Section: Resultsmentioning
confidence: 99%